Lumped Element Modeling of a Flexible Manipulator System - Kim, Sang-Myeong [UNESP] (Ieee-inst Electrical Electronics Engineers Inc, 2015)
This paper is concerned with a modeling method that can be used for an experimental identification of a dynamic system. More specifically, an equivalent lumped element system is presented to represent in a unique and exact manner a complete proportional-derivative (PD) controlled servo positioning system having a flexible manipulator. The impedance and mobility approach is used to transform the P and D control gains to an electrical spring and an electrical damper, respectively. The impedance model method is used to transform the flexible manipulator to a coupled system between a single contact mass at the driving position and a series of noncontact masses each of which is connected to the contact mass via a resilient member. This method is applicable whenever the driving point response of such a manipulator is available. Experimental work is presented to support the theory developed.
Keywords: Coupled mode analysis; impedance; manipulator dynamics; motion control; proportional-derivative (PD) control; vibration measurement